Novel Autism Spectrum Disorder (ASD) Risk Genes identified in Genome-Wide Association Studies (GWAS) through Protein Interaction Network analysis - Vicente, A.M. (2016)
ASD is a common disorder with heterogeneous clinical presentation and unclear etiology. Rare, highly penetrant, variants explain approximately 20% of ASD genetic liability, while common genetic factors of low effect, which combine in affected individuals to reach a pathological threshold, have proven more difficult to identify. The current GWAS data is consistent with the concept that common variant risk effects in ASD are too small to be detected with single SNP analysis. To uncover these variants from within the statistical “noise” in GWAS, new analysis strategies are needed. Disease-causing genes are expected to be functionally related, and therefore the proximity between gene products in a protein-protein interaction network can be used to distinguish relevant from spurious findings in GWAS.